Comparative Law Between Indonesia and Philippines Regarding the Procedure for Issuing Replacement Land Certificates - Dyah Adriantini Sintha Dewi; Tsuroyyaa Maitsaa’ Jaudah; Sigit Priyono; Princess Alysaa D. Tee-Anastacio (Jurnal Dinamika Hukum, 2025)
Land certificates are a fundamental aspect in ensuring legal certainty of land ownership. In practice, land certificates, although serving as strong legal evidence, are often damaged or lost, which can create new legal issues during the transfer of rights. In such cases, the rights holder may submit a request for a replacement certificate to the Land Office. This article compares the legal frameworks of Indonesia and the Philippines regarding procedures for issuing replacement certificates due to damage. In Indonesia, the replacement certificate is issued by the National Land Agency (BPN), whereas in the Philippines, the rights holder must file a petition to the court to obtain a recommendation for issuing a replacement certificate. This study employs a normative juridical method with a comparative legal approach and qualitative analysis of secondary data, including legislation, court decisions, and relevant legal literature. The findings show that the Administrative Court Decision No. 60/G/2023/PTUN.SMG declared that the issuance of replacement certificates by BPN in Pekalongan Regency violated legal provisions and the general principles of good governance. This indicates that although Indonesia’s system is faster and more efficient, it lacks strong legal safeguards. Meanwhile, the Philippines applies a slower, court-based process that ensures the validity of documents and provides stronger legal protection. Therefore, Indonesia needs to strengthen its procedures, improve internal oversight, and enhance transparency and accountability in the issuance of replacement land certificates